A simplified method for fundamental period prediction of steel frames with steel plate shear walls. (3rd March 2020) - Jiang, Rui; Jiang, Liqiang; Hu, Yi; Jiang, Lizhong; Ye, Jihong
Summary: Steel plate shear wall (SPSW) has been widely used as a lateral force resisting system (LFRS) for medium or high‐rise buildings. The fundamental period is an important parameter for seismic design and seismic risk assessment of building structures. In this paper, a simplified method is developed for the period prediction of SPSW structures based on the basic theory of engineering mechanics. It estimates a SPSW structure as a shear system of steel frame and a shear‐flexure system of SPSWs separately. The fundamental period of the SPSW structure is calculated according to the integration of the lateral stiffness of the steel frame and SPSWs along the height. A corrected formula is proposed based on the fitting analysis of the ratio of the FEM period to the estimated period. A shaking table test is used to validate the corrected formula, the relative error between the corrected result and the test result is 5.0%. Besides, the proposed method is also compared to some existing methods for the period prediction of SPSW structures, the results indicate that the proposed method has good accuracy and can be hand‐calculated. Finally, a probability‐based method is proposed for the corrected formula, and the fundamental period could be determined with a certain guarantee. A confidence interval estimation could be determined via the proposed method according to the demand of structural design.